2021
DOI: 10.1142/s0219720020500468
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of adverse drug reactions using drug convolutional neural networks

Abstract: Prediction of Adverse Drug Reactions (ADRs) has been an important aspect of Pharmacovigilance because of its impact in the pharma industry. The standard process of introduction of a new drug into a market involves a lot of clinical trials and tests. This is a tedious and time consuming process and also involves a lot of monetary resources. The faster approval of a drug helps the patients who are in need of the drug. The in silico prediction of Adverse Drug Reactions can help speed up the aforementioned process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Unpredictable reactions are not related to the dose or pharmacologic actions of the drug and occur mainly in susceptible individuals. They are divided into drug intolerance (undesirable pharmacologic effect that occurs at low or subtherapeutic doses), drug allergy and nonallergic reactions which result from direct release of mediators from mast cells and basophils [3,4].…”
Section: Introduction-surgery and Anesthesia-perioperative Eventsmentioning
confidence: 99%
“…Unpredictable reactions are not related to the dose or pharmacologic actions of the drug and occur mainly in susceptible individuals. They are divided into drug intolerance (undesirable pharmacologic effect that occurs at low or subtherapeutic doses), drug allergy and nonallergic reactions which result from direct release of mediators from mast cells and basophils [3,4].…”
Section: Introduction-surgery and Anesthesia-perioperative Eventsmentioning
confidence: 99%
“…It was found that recent papers can be classified into three types of databases, namely clinical [13], [18], [27], [33], registry [10], [12], [20], [24], [25], [29], [34], and knowledge [14], [15], [16], [17], [19], [21], [22], [23], [26], [28], [30], [31], [32], [35]. Additionally, based on review papers of existing XAI models [48], [49], the XAI algorithms used were divided into the following four categories: surrogate The main advantage of an explanatory technique such as SHAP is that it has solid roots in game theory, which ensures that the explanation of a prediction instance is fairly distributed across the features.…”
Section: ) Xai Methodsmentioning
confidence: 99%
“…For example, Kuang et al [7] built machine learning models using topological information from the drug-ADR associations network, drug chemical structures, and drug Anatomical Therapeutic Chemical (ATC) classification information to discover new drug-ADR associations. Anjani and colleagues [8] constructed a convolutional neural network model solely using drug chemical structures for the prediction of ADR occurrence. However, due to the absence of high-dimensional toxicity information such as ADR severity and frequency, current ADR prediction models are insufficient to comprehensively assess the true impact of drug toxicity on human health [9].…”
Section: Introductionmentioning
confidence: 99%